DETERMINANTS OF IPO UNDERPRICING IN THE INDONESIAN MARKET - Adzhary Dharmawan, Dzaky (PEOPLE: International Journal of Social Sciences, 2024)
This thesis studied the determinants of IPO underpricing in Indonesia by examining 277 IPOs in Indonesia from 2016-2022. This study found that firm age has a significant negative relationship with the level of underpricing while Covid-19 pandemic has significant positive relationship. We argue that information asymmetry and uncertainty explains the underlying reason behind our findings.